(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Introduction of Micro Finance Institutions (Development and Regulation) Bill, 2012 is a land mark in the history of Indian Microfinance Industry. This bill aims to provide for the development and regulation of microfinance institutions in India. One of the salient features of this bill is that all NBFCâ€MFIs must be members of at least one selfâ€regulatory organization (SRO) recognized by the RBI and comply with the code of conduct prescribed by the SRO. Even though the introduction of the Microfinance bill is a bit late, all the stakeholders appreciated and welcome the move of the Government. The microfinance industry in India is highly distributed and has many small players. The Reserve Bank of India (RBI) has limited presence on the ground. As the MFIs have businesses in the hinterland, there is a need for self-regulatory organizations (SROs) to enforce some self-discipline in the sector. An SRO is a voluntary body appointed by the industry participants to monitor the functioning of all players in the industry and bring in some degree of standardization in industry practices. These organizations operate under the overall regulatory supervision of the main regulator and help the main regulators in accomplishing their regulatory objectives. This mechanism provides an effective and efficient form of regulation in the constantly changing business environment because SROs virtually strive to strike an intelligent balance between the interest of its members and their regulatory responsibilities delegated by the main regulators. So, an SRO for microfinance institutions will play a complementary role to the Reserve Bank of India. Normally, this kind of entities knows the industry best and in many ways has the understanding, knowledge and ability to recognize a problem before it becomes too big. The authors made an attempt in this paper to provide a conceptual understanding on self-regulatory organizations (SROs), their functions and benefits, give clarity about SROs in Indian financial system in general and in Micro Finance Sector in particular. This paper also highlights the issues to be handled by RBI, while designing the policy frame work for SROs. Also focuses on contemporary challenges for self-regulatory organizations with a view to enable them to formulate strategies to overcome.